2000
DOI: 10.1074/jbc.m004900200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Interferon Consensus Sequence-binding Protein and COP9/Signalosome Subunit CSN2 (Trip15)

Abstract: Interferon consensus sequence-binding protein (ICSBP) is a member of the interferon regulatory factors (IRF) that has a pivotal role in mediating resistance to pathogenic infections in mice and in promoting the differentiation of myeloid cells. ICSBP exerts some of its transcriptional activities via association with other factors that enable its binding to a variety of promoters containing DNA composite elements. These interactions are mediated through a specific COOH-terminal domain termed IAD (IRF associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 50 publications
(79 reference statements)
2
29
0
Order By: Relevance
“…1A, compare lane 9 to lane 2). Further, we have also shown that serine 260 in IRF-8\ICSBP is essential for protein-protein interaction (21). Similar results are demonstrated here; mutation of this serine residue within the IAD of IRF-8\ICSBP eliminates its ability to negate IRF-1 (Fig.…”
Section: Both Irf-8\icsbp and Irf-4 Inhibit Irf-1-mediated Transcriptsupporting
confidence: 75%
See 2 more Smart Citations
“…1A, compare lane 9 to lane 2). Further, we have also shown that serine 260 in IRF-8\ICSBP is essential for protein-protein interaction (21). Similar results are demonstrated here; mutation of this serine residue within the IAD of IRF-8\ICSBP eliminates its ability to negate IRF-1 (Fig.…”
Section: Both Irf-8\icsbp and Irf-4 Inhibit Irf-1-mediated Transcriptsupporting
confidence: 75%
“…Our data also show that serine 260, which is unique to the IAD of IRF-8\ICSBP, is essential for this interaction, suggesting that the phosphorylation state of this residue is essential (for more details see Ref. 21). Tyrosine phosphorylation is also essential for proper activity of IRF-8\ICSBP.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…21,22 In mammals, CSN appears to be involved in important signal transduction pathways because of its ability to regulate protein kinases that phosphorylate c-Jun, p53, IB␣ and ICSBP/IRF-8. 21,[23][24][25] The phosphorylation of c-Jun and p53 requires direct binding to Jab1. 26 In addition, CSN cleaves the ubiquitinlike protein Nedd8 from the Cul1 subunit of the SCF 27 This "deneddylation" activity of CSN depends on the JAMM motif within the MPN domain of the Jab1/CSN5 subunit.…”
Section: Introductionmentioning
confidence: 99%
“…It resides primarily in the nucleus, although it may temporarily be in the cytoplasm (26). IRF-8 interacts with proteins of the Ets family, such as PU.1 and TEL, and regulates the development of myeloid cells (25,27).…”
mentioning
confidence: 99%